Exploring Grief through Visual Semiotics in “If Anything Happens I Love You” (2020) - Nofia; Syahra , Farkhatun; Agustina, Mia Fitria; Trisnawati, Ririn Kurnia (Universitas Airlangga, 2025)
If Anything Happens I Love You (2020) is a poignant animated short film that captures the overwhelming grief of parents who lose their child to a school shooting. This study analyzes the film using Roland Barthes’ visual semiotic theory, focusing on how signs within the film—particularly shadows, objects, and color—convey deeper emotional and ideological meanings. Through Barthes’ concepts of denotation, connotation, and myth, the analysis reveals that visual elements in the film serve not only as narrative tools but also as symbolic representations of trauma, memory, and the cultural construction of loss. Shadows embody internal emotional conflict, objects transform into memory vessels, and color evokes psychological states, all contributing to a layered storytelling experience. The findings suggest that the film utilizes visual semiotics to naturalize complex ideologies of grief and remembrance, allowing viewers to engage emotionally with a difficult subject through powerful, non-verbal communication.